NUEVAS ESPECIES CHILENAS DE XEROMELISSINAE (HYMENOPTERA: COLLETIDAE) - Toro, H. (Acta Entomológica Chilena, 2022)
Two new species of Chilimelissa are described: Ch. xanthorhina n.sp. from the Coastal area of northern Chile and Ch. machi n.sp. from the central part of the country. The description of the male of Ch. chillan Toro y Mold. 1979 and a key for the chilean species of the genus is also provided.